Patient perceptions of basic human needs fulfillment in hospitalized care: A study at Banda Aceh Hospital, Indonesia - Putra, Ardia; Kamil, Hajjul; Yuswardi, Yuswardi (International Journal of Innovative Research and Scientific Studies, 2025)
Nursing care focuses on meeting basic human needs, directly impacting patient satisfaction and healthcare quality. The objective of this study is to assess patients’ perceptions of the level of satisfaction they receive with their basic human needs while in a public hospital in Banda Aceh, Indonesia. This quantitative descriptive study was conducted using a cross-sectional design. Sixty-three patients were recruited using a proportional stratified random sampling method. Data were collected using a structured questionnaire and analyzed using descriptive statistics. The results indicated that 82.5% of patients perceived the fulfillment of their basic human needs as "good." The four most positively rated components were "eating and drinking sufficiently," "moving and maintaining position," "choosing appropriate clothing," and "maintaining body temperature within the normal range." The findings show that nurses are crucial in ensuring patients’ basic human needs are met by adequately implementing nursing procedures. Healthcare facilities must prioritize meeting patients’ fundamental needs by strengthening clinical nurses’ authority and enhancing nursing care protocols to improve patient outcomes and satisfaction.